2006
DOI: 10.1002/anie.200602035
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Cyclizations of Silyl Enol Ethers: Application to the Synthesis of (+)‐Lycopladine A

Abstract: In control: Gold(I)‐catalyzed intramolecular addition of silyl enol ethers to alkynes and allenes allows for the diastereoselective synthesis of cyclopentenes with control of the position of the double bond. The utility of these reactions is demonstrated by an efficient total synthesis of (+)‐lycopladine A that takes advantage of the orthogonal reactivity of AuI and Pd0 towards unsaturated iodides (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(65 citation statements)
references
References 55 publications
0
64
0
1
Order By: Relevance
“…Our group first reported a highly efficient Au(I)-catalyzed Conia-ene reaction in 2004, 4 which, along with work by Echavarren on the addition of enol ethers into alkynes, demonstrated that π-acids were highly competent catalysts for the addition of electron-rich alkenes into unactivated π-systems. 5 Further work in our group has led to the development of Pd(II)- and Au(I)-catalyzed enantioselective variants of these transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Our group first reported a highly efficient Au(I)-catalyzed Conia-ene reaction in 2004, 4 which, along with work by Echavarren on the addition of enol ethers into alkynes, demonstrated that π-acids were highly competent catalysts for the addition of electron-rich alkenes into unactivated π-systems. 5 Further work in our group has led to the development of Pd(II)- and Au(I)-catalyzed enantioselective variants of these transformations.…”
Section: Introductionmentioning
confidence: 99%
“…These are the catalytic agents in a broad range of transformations at unsaturated carbon centers, primarily alkynes and allenes. Oftentimes a (phosphine)-or (N-heterocyclic carbene)gold(I) cation is formed in situ by halide abstraction with silver(I) reagents (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). An immediate complication is the fate of silver, which itself has a notorious affinity for unsaturated carbon.…”
mentioning
confidence: 99%
“…In this case, the distance between phosphine and substrate-binding sites is decreased to 3.14 A (versus 4.58 A for the Au(I) catalyst). We subsequently applied the principles we had learned in developing the Au(I)- and Pd(II)-catalyzed Conia-ene reactions to include transformations employing silyl enol ethers as nucleophiles 15. This methodology was subsequently applied to total synthesis of (+)-lycopladine A and (+)- fawcettimine 16…”
Section: Addition Reactionsmentioning
confidence: 99%